Evaluation of the dynamic behavior of a GFRP-SFRSCC hybrid footbridge - Gonilha, José (2011)
This paper presents results of numerical investigations on the dynamic behaviour of a hybrid footbridge made of glass fiber reinforced polymer (GFRP) pultruded profiles and a steel fibre reinforced self-compacting concrete (SFRSCC) slab. Finite element (FE) models were developed to simulate the dynamic response of the footbridge when subjected to human induced vibrations. Results obtained were compared with requirements defined in several standards in order to verify the performance of the footbridge regarding the fulfilment of comfort criteria. In addition, direct and indirect verification methods were compared to assess the applicability of the latter when used with GFRP-SFRSCC hybrid structures.